2017
DOI: 10.1007/s00464-017-5604-z
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous cholecystitis: Is an initial laparoscopic approach feasible?

Abstract: An initial laparoscopic approach is possible for xanthogranulomatous cholecystitis. However, it is troublesome and challenging, with significantly higher conversion and complication rates compared to standard laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
5
19
2
Order By: Relevance
“…The average operative times were 127 min for OC, 82 min for LC and 141 min for LOC. All these times are similar to those published by other authors, and are longer than those corresponding to patients without XGC, according to the data reported previously . The conversion rate for laparoscopic cholecystectomy in patients without XGC commonly varies between 2 and 10 per cent .…”
Section: Discussionsupporting
confidence: 90%
“…The average operative times were 127 min for OC, 82 min for LC and 141 min for LOC. All these times are similar to those published by other authors, and are longer than those corresponding to patients without XGC, according to the data reported previously . The conversion rate for laparoscopic cholecystectomy in patients without XGC commonly varies between 2 and 10 per cent .…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, few studies have reported outcomes of LC for XGC (summarized in Table III) (7)(8)(9)(10)(11)(12)(13)(14)(15). Our study included a relatively large number of patients that underwent LC (38 cases) compared to most other studies (range, 7-47 patients).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that, compared to open cholecystectomy, LC was associated with a lower postoperative complication rate and shorter postoperative hospital stay (4)(5)(6). However, few studies have investigated the surgical outcome of LC treatments for XGC; furthermore, the outcome has been an issue of controversy (7)(8)(9)(10)(11)(12)(13)(14)(15). For example, in patients undergoing LC for XGC, the various reported rates of converting from laparoscopic surgery to open surgery have ranged between 10 and 80%, which gave rise to the controversy.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthogranulomatous cholecystitis is an inflammatory disease characterized by the accumulation of lipid-laden macrophages, fibrous tissue, acute and chronic inflammatory cells. It may mimic gallbladder cancer as involvement in neighboring organs (20). It has also been reported that there is a relationship between xanthogranulomatous cholecystitis and carcinoma of the gallbladder cancer (21).…”
Section: Discussionmentioning
confidence: 99%